The Influence Of Digital Marketing And Brand Image On The Competitiveness Of Micro, Small, And Medium Enterprises (Msmes) Among Generation Z At The Pondok Jawi Restaurant In Lahat - Putri Larasati; Marko Ilpiyanto; Titi Hasanah (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the influence of digital marketing and brand image in increasing the competitiveness of MSMEs among Generation Z at Pondok Jawi Restaurant, Lahat. The results showed that (1) digital marketing has a significant partial effect on competitiveness, as evidenced by the calculated t value > t table (7.250 > 1.989). (2) brand image has a significant partial effect on competitiveness, as evidenced by the calculated t value > t table (3.298 > 1.989). (3) digital marketing and brand image have a significant simultaneous effect on competitiveness, as evidenced by the calculated f value > f table (61.564 > 3.956), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).